2016
DOI: 10.1016/j.bpj.2015.11.168
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of the Initiation of RNA Polymerase II Transcription

Abstract: impair electron transport complexes, and lead to neuronal apoptosis. Recently, using a channel reconstitution technique, we demonstrated that monomeric asyn both reversibly blocks and translocates through the voltage-dependent anion channel (VDAC) at nanomolar concentrations. Considering VDAC's major role in regulating metabolite fluxes across the MOM, a functional interaction between a-syn and VDAC could be essential for physiological adaptation of mitochondria and dysfunction in PD. Here we show that the asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…5). Moreover, biochemical studies have shown a requirement for TFIIH activity even after conversion from the closed to open promoter complex (23,24), and realtime observations of single PICs have demonstrated DNA translocation and duplex melting for dozens of base pairs following the initiation of transcription (25). Such continuation of TFIIH helicase activity can only occur if the paths of DNA in the PIC and in a transcribing complex coincide.…”
Section: Discussionmentioning
confidence: 99%
“…5). Moreover, biochemical studies have shown a requirement for TFIIH activity even after conversion from the closed to open promoter complex (23,24), and realtime observations of single PICs have demonstrated DNA translocation and duplex melting for dozens of base pairs following the initiation of transcription (25). Such continuation of TFIIH helicase activity can only occur if the paths of DNA in the PIC and in a transcribing complex coincide.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time records were truncated to display only those segments acquired under constant (low) loads. Tether extension data were low-pass filtered (end of pass band = 0.1 Hz; start of reject band = 50 Hz, number of coefficients = 500) 21 , and the extension changes were converted to positions along the hairpin relative to the TSS, using established methods 27,28 . In performing this conversion, the extension under low load (when the hairpin is fully folded) was selected as the reference extension, which was then used as the starting point for real-time records.…”
Section: Methodsmentioning
confidence: 99%
“…Previous structural, biochemical, and biophysical studies [13][14][15][16][17] have provided snapshots of holoenzyme-promoter contacts, and a variety of single-molecule approaches have proved useful in dissecting additional mechanistic and kinetic details of initiation in prokaryotes 3,4,[18][19][20] and eukaryotes 21 , but key questions remain. In particular, how does RNAP remodel its contacts with the promoter DNA during the initiation phase, ultimately leading to the formation of the EC?…”
mentioning
confidence: 99%
“…A recent study by Fazal and colleagues reported an extraordinary achievement of assembling a 32-protein pre-initiation complex (PIC), in real time, using optical tweezers to study the initiation of yeast RNA polymerase II (Pol II) (10). The complex consisted of Pol II and six general transcription factors, including TATA-binding protein, TFIIB, TFIIE, TFIIF, TFIIH and TFIIA and Sub1 ( Figure 2A).…”
Section: Studies Of Transcription Initiationmentioning
confidence: 99%
“…Third, with single-molecule techniques it is possible to measure highly dynamic and fast movements, given the high spatiotemporal resolution that has become available (7). Fourth, individual molecules can be perturbed and manipulated in specific ways by force, and the response of an individual molecule to applied external force can be recorded (8)(9)(10)(11)(12). Therefore, single-molecule techniques enable the acquisition of precise and quantitative data, which allows the verification of biophysical theoretical models of transcription a dynamics and regulation.…”
Section: Introductionmentioning
confidence: 99%